Phenotype and Response to PAMPs of Human Monocyte-Derived Foam Cells Obtained by Long-Term Culture in the Presence of oxLDLs - Nogieć, Anna; Bzowska, Małgorzata; Demczuk, Agnieszka; Varol, Chen; Guzik, Krzysztof (Frontiers in Immunology, 2020)
Cholesterol-laden, foam macrophages constitute the most characteristic component of human atherosclerotic plaques. Persistent uptake of oxLDLs results in accumulation of lipid bodies inside the cells and determines their phenotype and subsequent functions. In this work, we describe the phenotype of human monocyte-derived foam cells obtained by differentiation in the constant presence of oxLDLs for thirty days (prolonged-hMDFCs). Although neither the total cellular nor the cell surface expression of Toll-like receptors (TLR) was regulated by oxLDLs, the prolonged-hMDFCs changed dramatically their responsiveness to TLR ligands and inactivated bacteria. Using multiplex technology, we observed an acute decline in cytokine and chemokine production after surface and endosomal TLR stimulation with the exception of TLR2/6 triggering with agonists Pam2CSK4 and MALP-2. We also noted significant reduction of some surface receptors which can have accessory function in recognition of particulate antigens (CD47, CD81 and CD11b). In contrast, the prolonged-hMDFCs responded to inflammasome activation by LPS/nigericin with extensive, necrotic type cell death, which was partially independent of caspase-1. This pyroptosis-like cell death was aggravated by necrostatin-1 and rapamycin. These findings identify a potential contribution of mature foam cells to inflammatory status by increasing the immunogenic cell death burden. The observed cross-talk between foam cell death pathways may lead to recognition of a potential new marker for atherosclerosis disease severity. Overall, our study demonstrates that, in contrast to other cellular models of foam cells, the prolonged-hMDFCs acquire a functional phenotype which may help understanding the role of foam cells in the pathogenesis of atherosclerosis.